2019
DOI: 10.9745/ghsp-d-18-00407
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Quality of Contraceptive Counseling and Method Continuation: Findings From a Prospective Cohort Study in Social Franchise Clinics in Pakistan and Uganda

Abstract: Higher scores on the 3-question Method Information Index (MII)—measuring client-reported receipt of contraceptive information—was associated with continued use of family planning over 12 months. We recommend incorporating use of the MII in routine assessments of family planning service quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…The highly significant association between a positive MII score and LARC adoption suggests the importance of information for decision-making and method use. Another recent study found a similar positive relationship between quality of information exchanged as measured by MII and method continuation; 22 however, the research using MII is still limited. It should also be noted that only 28% of women interviewed for this study answered "yes" to all three questions in the MII, suggesting more progress is needed in providing adequate information to women adopting a contraceptive method in Lomé.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The highly significant association between a positive MII score and LARC adoption suggests the importance of information for decision-making and method use. Another recent study found a similar positive relationship between quality of information exchanged as measured by MII and method continuation; 22 however, the research using MII is still limited. It should also be noted that only 28% of women interviewed for this study answered "yes" to all three questions in the MII, suggesting more progress is needed in providing adequate information to women adopting a contraceptive method in Lomé.…”
Section: Discussionmentioning
confidence: 76%
“…There is a growing body of evidence to support the notion that improving the quality of care of FP services is key to increasing use and continuation of FP services, particularly in resource limited settings. 22,26,33 However, evidence on which factors are most important in determining quality of FP services is still sparse. 26 In this study, we set out to assess if the quality of FP service provision, both of program performance and program capacity, influenced LARC adoption in Lomé, Togo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many tools to assess the quality of FP services, however, there is lack of agreement on their routine use (Sprockett 2017). Recent studies have validated quality measures appropriate for routine reporting in FP service delivery settings, finding that higher values on the FP quality measures were associated with increased contraceptive use and reduced discontinuation (Jain et al, 2013;Jain and Winfrey, 2017;Chakraborty et al, 2019;Jain et al, 2019;Holt et al, 2019). While the evidence and the validated metrics are promising, measurement of rights such as client autonomy in service delivery settings can be further improved (Bertrand et al, 2014;Cole et al, 2019).…”
mentioning
confidence: 99%